PERAN SEORANG GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF - Jumrawarsi, Jumrawarsi; Suhaili, Neviyarni (Ensiklopedia Education Review, 2020)
Conducive learning situation is related to the quality of students learning. The creation of a conducive class will avoid students from feeling bored, psychic exhaustion and also the creation of a conducive class that will provide students motivation and learning convernience. In an active learning condition, students do not feel alone solving cases faced in the learning process, but the students can ask the question to other and discuss each other so that their learning load does not occur. With the existence of an active learning strategy, it is hoped that it can grow all the potential possessed by students so that in the end they can optimize their learning outcomes. hance, The teacher as a guide has very important role in Learning process. Teachers must be able to give students motivation to create a process of interaction that is conducive to the learning process in the classroom. In the interactive teaching and learning process, there is an interaction between students and students and students and teachers.